The affections in the research: performatic becomings in education (Praxis Educativa, 2022)
As a sensory voice that confuses the sovereign subject with the atmospheres of their environments, the erotic becoming in the disciplinary normativity of educational research, performs how we get involved in a research with our desires. Epistemically, in this article, we counter-interpret autobiographic erotic riches from the narrative exercise of renouncing the sovereign conscience of its enunciators. The de-identification of the researcher is valued, for this, as an expansion of the linearities of the realistic interpretation of the affects.